Routine Surveillance for Bloodstream Infections in a Pediatric Hematopoietic Stem Cell Transplant Cohort: Do Patients Benefit?. Issue 4 (2007) - Rigby, Heather; Fernandez, Conrad V; Langley, Joanne; Mailman, Tim; Crooks, Bruce; Higgins, Ann
Abstract : BACKGROUND: Hematopoietic stem cell transplant (HSCT) recipients are at a high risk for late bloodstream infection (BSI). Controversy exists regarding the benefit of surveillance blood cultures in this immunosuppressed population. Despite the common use of this practice, the practical value is not well established in non-neutropenic children following HSCT. METHODS: At the IWK Health Centre (Halifax, Nova Scotia), weekly surveillance blood cultures from central lines are drawn from children following HSCT until the line is removed. A retrospective chart review was performed to determine the utility and cost of this practice. Eligible participants were non-neutropenic HSCT recipients with central venous access lines. The cost of laboratory investigations, nursing time, hospital stay and interventions for positive surveillance cultures was calculated. RESULTS: Forty-three HSCTs were performed in 41 children. Donors were allogenic in 33 cases (77%) and autologous in 10 cases (23%). There were 316 patient contacts for surveillance cultures (mean seven per patient) and 577 central line lumens sampled. Three of 43 patients (7%) had clinically significant positive surveillance blood cultures. Bacteria isolated were Klebsiella pneumoniae (n=2) and Corynebacterium jeikeium (n=1). All follow-up cultures before initiation of antimicrobial therapy were sterile. All three patients were admitted for antimicrobial therapy if they were not already hospitalized and/or had an uncomplicated course. The estimated total cost of BSI surveillance and management of asymptomatic infection over six years was $27, 989. CONCLUSION: The present study suggests that BSI surveillance in children following HSCT engraftment has a very low yield and significant cost. It is unclear whether it contributes to improved patient outcomes.